The labour market integration of refugee and family reunion immigrants: A comparison of outcomes in Canada and Sweden - Pieter Bevelander; Ravi Pendakur (Institute for the Study of Labor (IZA), 2012)
This paper assesses the employment and earnings trajectories of refugee and family reunion category immigrants in Canada and Sweden using two national level sources of data. The Canadian Immigration Database (IMDB) is a file that links the intake record of post 1979 immigrants with annual taxation records. The 2007 Swedish Register Data includes information on all legal permanent residents. Using standard regression methods we compare labour force outcomes of age-sex-schooling-place of birth cohorts looking specifically at non-economic (family reunion and refugee intake) immigrants from Iran, Iraq, Afghanistan and the former Yugoslavia. We find that the employment and earning trajectories of the selected non-economic migrant groups are quite similar in the two host countries, although earnings are higher in Canada than in Sweden.
Keywords: F22; J61; J68; 330; refugees; immigrants; family reunion; labour market integration; comparison; Flüchtlinge; Einwanderung; Familie; Berufliche Integration; Arbeitsmarkt; Vergleich; Kanada; Schweden